Penggunaan komputer di kalangan guru-guru Sekolah Menengah di Bandaraya Kuching Utara - Azhar, Bin Hj. Ahmad (UNIMAS, 1998)
This is an exploratory study regarding the usage of computer among teachers in secondary schools in Kuching City North, Sarawak. The aims of this research are to identify the attitude of the teachers toward computers, to identify the difference of attitude towards computers based on the subjects taught, gender, computer ownership and teaching experience and to identify the relationship between the attitude towards computers and the independent variables i.e . academic, level professional training, computer training, assignments at schools, assignments related to the use computer and the level of computer competency as perceived by the samples. 155 teachers teaching Islamic Education and Science subject from eleven secondary schools in Kuching city North participated in this study.